Evaluating radiocarpal cartilage matrix changes 3‐months after anti‐TNF treatment for rheumatoid arthritis using MR T1ρ imaging. Issue 5 (23rd September 2016) - Ku, Eric; Pedoia, Valentina; Tanaka, Matthew; Heilmeier, Ursula; Imboden, John; Graf, Jonathan; Link, Thomas; Li, Xiaojuan
Abstract : Purpose: To evaluate the feasibility of MR T1ρ in assessing radiocarpal cartilage matrix changes following rheumatoid arthritis (RA) treatment. Materials and Methods: Five healthy controls and nine RA patients were studied: three RA patients with low disease activity that were treated with methotrexate (MTX) alone and six with active disease despite MTX treatment who were additionally treated with certolizumab pegol, an anti‐tumor necrosis factor biologic. Wrist 3 Tesla MRI were acquired at baseline and 3‐month follow‐up. T1ρ were quantified for lunar, radius, and scaphoid cartilage. Reproducibility was evaluated using coefficients of variation (CV). Longitudinal changes were evaluated with t‐test and relationships between T1ρ with clinical, MRI, and patient‐reported outcomes were evaluated with Spearman's rho. Results: Scan/re‐scan CVs of T1ρ values were all <5%, and intra‐ and inter‐reader CVs were all < 2.0%. Baseline scaphoid T1ρ values were significantly higher in RA patients compared with healthy controls ( P  = 0.032). Changes in T1ρ (baseline, 3‐month) were correlated with EULAR treatment response criteria: −2.26 ± 0.75 ms, 1.08 ± 0.52 ms, and 2.18 ± 0.45 ms for good, moderate, and nonresponders, respectively. Significant correlations were found between changes in global T1ρ values and changes in DAS28‐CRP (rs  = 0.683; P  = 0.042), MHQ (rs  = −0.783; P  = 0.013), and HAQ (rs  = 0.833; P  = 0.010). Conclusion: Despite the limited sample size and follow‐up time points, there were significant correlations between changes in radiocarpal T1ρ and changes in disease activity as assessed by clinical and patient‐reported outcomes. Our findings encourage further research into MR T1ρ assessment of RA disease activity and treatment response. Level of Evidence : 1 J. MAGN. RESON. IMAGING 2017;45:1514–1522